Inflammatory response of feedlot cattle to clostridial vaccination: a comparison of 7-way bacterin-toxoid and C&D toxoid - Gerald L. Stokka; Robert T. Brandt Jr.; A.J. Edwards; M.F. Spire; J.E. Smith (Kansas Agricultural Experiment Station Research Reports, 1993)
Twenty-four finishing steers (758 lb) were subcutaneously vaccinated and revaccinated 31 days later with 1) sterile saline, 2) a clostridial perfringens C&D toxoid, or 3) a 7-way clostridial bacterin-toxoid to evaluate the effects of vaccine type on inflammatory response in feedlot cattle. Injection site reactions were most severe (P<.05) and persistent for 7-way bacterin-toxoid and were accompanied by elevated (P<.05) blood haptoglobin levels indicative of acute inflammation. Revaccination with 7-way bacterin-toxoid reduced (P<.05) feed consumption for a 4-day period postvaccination. Although some reactions were severe, they appeared transient because blood parameters and volume of injection site reactions returned to baseline levels 25 to 60 days after injection. Performance over the entire feeding period was not significantly altered by treatment. We strongly recommend that clostridial products be used subcutaneously only, to minimize potential damage to carcass tissue from intramuscular injection.
Keywords: Cattlemen' s Day; 1993; Kansas Agricultural Experiment Station contribution; no. 93-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 678; Beef; Vaccination; Cattle; Injection site